Peter C. Petersen letter to Michael C. Newlon regarding fall birds sighted, November 30, 1984 - Petersen, Peter C.et al (1984)
Peter C. Petersen letter to Michael C. Newlon regarding fall birds sighted, November 30, 1984. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed